Unveiling the Mysteries of Pharmacoreincarnation: A Study on the Spiritual and Metaphysical Dimensions of Using Psychoactive Drugs for Accessing Past Life Memories - Fendy Prasetyawan; Nanda Ardianto; Yuneka Saristiana; Wahyu Ariawan; Faisal Akhmal Muslikh; Yunita Dian Permatasari (Paspama Institute, 2023)
The research delves into the multifaceted realm of psychoactive drugs, spirituality, and the exploration of past life memories, known as